A New Record of Saxifraga afghanica Aitch. & Hemsl. (Saxifragaceae) in Iraq - Sardar, Abdullah Sh. (Iraqi Journal of Science, 2022)
Saxifraga afghanica Aitch. & Hemsl. is a new addition to the Saxifragaceae family in Iraq, from Qandil mountain (north-east of Erbil) within Rowanduz district (MRO). The collected specimens have different characteristics. S. afghanica is perennial, herb, with crowded shoots forming cushions, many branched. Leaves sessil, narrowly oblong, narrowly oblong-lanceolate, oblanceolate or sub-spatulate, glabrous, entire, ciliated at lower half, apex leaves aggregated into a rosette, chalk glands (pits at the leaves apex) 5. Bracts cultrate, linear or narrowly oblong, glandular-pubescent. Inflorescence corymbose cyme, flowers (3-5), white-pink, stamens 10, ovary semi-inferior, styles 2, divergent, recurved at the top. Capsule globose-semi globose. Identification, morphological study was conducted, these reinforced by graphs. In addition, some characters of the pollen grains have been studied such as shapes, colors, sizes, numbers and surface sculpture.